2020
DOI: 10.3389/fmars.2020.540165
|View full text |Cite
|
Sign up to set email alerts
|

Open-Ocean Minima in δ13C Values of Particulate Organic Carbon in the Lower Euphotic Zone

Abstract: Extensive studies in the 1980s-1990s led to the characterization of latitudinal variations in sea surface δ 13 C values of particulate organic carbon (δ 13 C POC), and relationships were found with CO 2 concentrations, temperature, growth rates, and cell geometries. Surprisingly, no large-scale efforts have been made to describe variations in δ 13 C POC values over depth in the water column. Here we compile published examples demonstrating a widespread isotopic pattern in particulate organic carbon (POC) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…The vertical distribution of POC is closely related to the biogeochemical processes at each water depth. Photosynthesis is the main source of POC in the upper waters of the ocean (Song, 2010;Close and Henderson, 2020). In this study, POC and Chla concentrations showed a significant positive correlation in the water column of 0-300 m (r 0.339, p < 0.01, n 139), which further indicated the close relationship between POC and phytoplankton in the upper waters of the Kocebu seamount area.…”
Section: The Production and Decomposition Of Pocsupporting
confidence: 65%
See 3 more Smart Citations
“…The vertical distribution of POC is closely related to the biogeochemical processes at each water depth. Photosynthesis is the main source of POC in the upper waters of the ocean (Song, 2010;Close and Henderson, 2020). In this study, POC and Chla concentrations showed a significant positive correlation in the water column of 0-300 m (r 0.339, p < 0.01, n 139), which further indicated the close relationship between POC and phytoplankton in the upper waters of the Kocebu seamount area.…”
Section: The Production and Decomposition Of Pocsupporting
confidence: 65%
“…In the water column of 500-1,000 m, although the POC continued to decrease, its decomposition rate was significantly lower than that in the water column of 150-300m. The reason for this phenomenon may be that the easily degradable POC was decomposed in the shallower water column, whereas the remaining POC in the deeper water column was difficult to decompose (Close and Henderson, 2020;Weber and Bianchi, 2020). In addition, it may also be caused by a significant decrease in the seawater temperature and DO.…”
Section: The Production and Decomposition Of Pocmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent collection of 303 measurements of δ 13 C POC has been provided by Close and Henderson (2020), largely based on data gathered from individual publications referenced therein. Since our analyses originally relied on data sources that differed from those of Close and Henderson (2020), we find our collection to be as yet incomplete. Especially measurements from national databases might provide a huge future benefit.…”
Section: Data Sourcesmentioning
confidence: 99%